Emulsion-based edible chitosan film containing propolis extract to extend the shelf life of strawberries - Akkuzu, Nisa; Karakas, Canan Yagmur; Devecioglu, Dilara; Guler, Funda Karbancioglu; Sagdic, Osman; Karadag, Ayse (ELSEVIER, 2024)
In this study, propolis was first loaded into a conventional oil-in-water emulsion, which was combined with a chitosan film-forming solution to produce propolis emulsion-loaded film (PEF). Strawberries inoculated with Botrytis cinerea coated with PEF and blank emulsion-loaded films (BEF) were stored for 14 days at 4 degrees C. Compared to BEF, PEF showed superior mechanical and oxygen barrier properties, as well as antioxidant activities, but higher moisture permeability. PEF showed less oil agglomeration on the film surface after drying, as demonstrated by scanning electron microscopy (SEM) analysis. Compared to uncoated strawberries, coatings did not have a significant effect on weight loss or firmness during storage. In contrast, coated strawberries showed elevated total phenolics, anthocyanins, and ascorbic acid retention; however, PEF-coating yielded higher values. Moreover, the PEF coating resulted in a significantly lower reduction of organic acid and total soluble solids. Mold growth was visible in both uncoated and BEF-coated strawberries after 7 days of storage, while PEF-coated fruits showed no visible mold until the end of storage. Starting from day 4, PEF-coated fruits showed lower mold counts (similar to 2 log CFU/g) than other samples. Therefore, the PEF prepared in this study has application potential for the preservation of fresh fruits.
Keywords: Edible coating; Botrytis cinerea; Antifungal activity; Storage; ANTIOXIDANT ENZYME-SYSTEM; BIOACTIVE COMPOUNDS; QUALITY; FRUIT; ACID; COATINGS; Biochemistry & Molecular Biology; Chemistry; Polymer Science